QUALITY OF LIFE, CLINICAL AND BIOCHEMICAL PARAMETERS IN HYPERTENSIVE PATIENTS WITH COMORBID CONDITIONS - E. B. Akhmedova; B. U. Mardanov; K. K. Badeynikova; M. N. Mamedov (Столичная издательская компания, 2017)
Aim. To study the socio-behavioral, instrumental and laboratory parameters and quality of life of patients with arterial hypertension (HT) and comorbid conditions.Material and methods. The study included 64 patients of both  sexes, aged  30-69 years. All patients were divided into 3 groups:  patients with HT (I group, n=20; 52.7±9.9 years old); patients with HT and diabetes mellitus (DM) type 2 (II group, n=23; 58±5.3 years old); and HT patients with chronic obstructive pulmonary disease (COPD; III group, n=21; 57±7.2 years old). Clinical symptoms, anamnesis, resting heart  rate were evaluated as well as blood pressure measurement, echocardiography and biochemical analysis of the blood were performed. Quality of life was also assessed with the international questionnaire EQ-5D.Results. Combination of HT and COPD was more common in women than in men (66.7% vs 33.3%), and a body mass index >30  kg/m2 was typical for the majority of patients with the HT and DM (34.1±9.1 kg/m2), HT and COPD (33.6±6.7 kg/m2). The assessment with the questionnaire EQ-5D showed that a more pronounced decrease in the quality of life was in patients with HT and DM. Quality of life in groups  II and III was worse than  in group  I (1.7±1.3 and 1.4±1.5 vs 0.9±0.86 scores,  respectively). The combinations of HT with DM and HT with COPD were accompanied by increased plasma creatinine levels (88.6±14 and 88.5±11.7 mcmol/L, respectively) and more severe dyslipidemia.Conclusion. In patients with HT concomitant DM and COPD contribute to the quality of life reduction, increase in plasma creatinine levels, and more severe dyslipidemia.